PROCESS MODELING OF SULPHURIC ACID LEACHING OF IRON FROM OZORO CLAY - Henry, Orugba O.; Onukwuli, Okechukwu D.; Chigoziri, Njoku N.; Kelvin, Ojebah C.; I.A., Nnanwube (European Scientific Journal, ESJ, 2014)
The local clay from Ozoro (6.24oN, 5.55oE) in Delta State Nigeria is relatively rich in iron content. The traditional method of obtaining optimum leaching conditions by varying just one factor at a time while keeping the rest constant is cumbersome and does not save time This research work was aimed at investigating the combined effects of calcinations temperature, leaching temperature, acid concentration, liquid-solid ratio and stirring speed on iron yield from the local clay in H2SO4using the Response Surface Methodology. The result obtained showed that the second order polynomial regression equation fitted the experimental data more appropriately with a correlation coefficient R2 of 0.9189. The optimum conditions were calcinations temperature of 650oC; leaching temperature of 70.02oC; acid concentration of 1.89mol/cm3; liquid-solid ratio of 10.67 and stirring speed of 379.80rpm at an optimum yield of 84.7%.